The inhibitory effect of 6-gingerol and cisplatin on ovarian cancer and antitumor activity: In silico, in vitro, and in vivo - Salari, Zohreh; Khosravi, Ahmad; Pourkhandani, Elham; Molaakbari, Elaheh; Salarkia, Ehsan; Keyhani, Alireza; Sharifi, Iraj; Tavakkoli, Hadi; Sohbati, Samira; Dabiri, Shahriar; Ren, Guogang; Shafie’ei, Mohammad (Frontiers in Oncology, 2023)
Background Epithelial ovarian cancer is very common in women and causes hundreds of deaths per year worldwide. Chemotherapy drugs including cisplatin have adverse effects on patients’ health. Complementary treatments and the use of herbal medicines can help improve the performance of medicine. 6-Gingerol is the major pharmacologically active component of ginger. In this study, we compared the effects of 6-gingerol, cisplatin, and their combination in apoptotic and angiogenetic activities in silico, in test tubes, and in in vivo assays against two ovarian cancer cell lines: OVCAR-3 and human umbilical vein endothelial cells (HUVECs). Methods The drug-treated cell lines were evaluated for their cytotoxicity, cell cycle, and apoptotic and angiogenetic gene expression changes. Results The proportion of apoptosis treated by 6-gingerol coupled with cisplatin was significantly high. In the evaluation of the cell cycle, the combination therapy also showed a significant promotion of a higher extent of the S sequence. The expression of p53 level, Caspase-8, Bax, and Apaf1 genes was amplified again with combination therapy. Conversely, in both cell lines, the cumulative drug concentrations reduced the expression of VEGF, FLT1, KDR, and Bcl-2 genes. Similarly, in the control group, combination treatment significantly decreased the expression of VEGF, FLT1, KDR, and Bcl-2 genes in comparison to cisplatin alone. Conclusions The findings of the present study demonstrated that the cisplatin and 6-gingerol combination is more effective in inducing apoptosis and suppressing the angiogenesis of ovarian cancer cells than using each drug alone.